Sustainable fabrication of lightweight geopolymer foams from silica-fume and zeolite tuffs: Utilizing Al as foaming agent for thermal insulation - Jamal-Eldin F.M. Ibrahim; Ethem İlhan Şahin; Mohamed A. Basyooni-M. Kabatas; Róbert Géber; István Kocserha (Case Studies in Construction Materials)
In response to the increasing demand for eco-friendly thermal insulation materials in construction, this research focuses on the development of geopolymer foams with optimized thermal insulation properties. The study employs silica fume and zeolite tuff as primary raw materials, activated by sodium hydroxide and sodium silicate solution, and incorporates aluminum powder and sodium lauryl sulfate (SLS) as additives to enhance porosity and refine pore size distribution. A comprehensive analysis of technical properties, including compressive strength, porosity, bulk density, and thermal conductivity, is conducted to assess the influence of these additives. The findings demonstrate that SLS plays a main role in modifying the microstructure, resulting in more uniform and interconnected pores. The addition of moderate amounts of SLS (0.9 wt%) promotes the formation of consistent cell sizes and porosity, contributing to the overall structural integrity of the foams. The foams are predominantly amorphous, with some residual crystalline phases observed. Scanning electron microscopy (SEM) reveals the development of sodium aluminum silicate whiskers, which serve as reinforcement, enhancing the mechanical strength of the geopolymer matrix. The resulting geopolymer foams exhibit high porosity (64.36–81.32 %), low thermal conductivity (0.29–0.07 W/m·K), and sufficient compressive strength (0.96–2.71 MPa), indicating their potential as sustainable insulation materials for construction applications.